2015
DOI: 10.1093/schbul/sbv022
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aerobic Exercise on Brain-Derived Neurotrophic Factor and Neurocognition in Individuals With Schizophrenia: A Single-Blind, Randomized Clinical Trial

Abstract: Individuals with schizophrenia display substantial neurocognitive deficits for which available treatments offer only limited benefits. Yet, findings from studies of animals, clinical and nonclinical populations have linked neurocognitive improvements to increases in aerobic fitness (AF) via aerobic exercise training (AE). Such improvements have been attributed to up-regulation of brain-derived neurotrophic factor (BDNF). However, the impact of AE on neurocognition, and the putative role of BDNF, have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
1
9

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(187 citation statements)
references
References 69 publications
8
169
1
9
Order By: Relevance
“…Also, the increased risk of physical illnesses in patients with mental disorders [6] underlines the great importance of improvements of physical performance in schizophrenia. The finding of increased endurance capacity in patients with schizophrenia after endurance training is in agreement with other studies [21,24,[37][38][39][40][41][42][43][44] though in some studies, the methods are poorly described and the quality of the results cannot be judged properly. Still, to our knowledge no study to date has demonstrated these improvements with the set of outcome parameters used in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, the increased risk of physical illnesses in patients with mental disorders [6] underlines the great importance of improvements of physical performance in schizophrenia. The finding of increased endurance capacity in patients with schizophrenia after endurance training is in agreement with other studies [21,24,[37][38][39][40][41][42][43][44] though in some studies, the methods are poorly described and the quality of the results cannot be judged properly. Still, to our knowledge no study to date has demonstrated these improvements with the set of outcome parameters used in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Future research should target these therapeutic effects of endurance training more specifically with the goal to subsequently use training purposefully in therapeutic regimens. Some therapeutic effects of exercise have already been shown in schizophrenia, for example improved neurocognition [10,42,59]. Single studies and meta-analyses reported positive effects of physical activity on schizophrenia symptoms and everyday functioning [13,14,38,60,61].…”
Section: Future Researchmentioning
confidence: 98%
“…Previous research [37,38] suggested that aerobic fitness improvements following exercise might be a testable mechanism. Kimhy et al [39] showed recently that the increased production of brain-derived neurotrophic growth factors (BDNF) following aerobic fitness improvements probably plays a particular role. More interventional and longitudinal exploration of the underlying mechanisms for brain health improvements in patients with schizophrenia following a physical exercise program is needed.…”
Section: What Are the Mechanisms Of The Physical Activity Effects In mentioning
confidence: 99%
“…Trainers can foster their rhythms through the interaction with the computer. With our approaches, the digitalization and informatization of basic aerobics training and other training levels can be further developed [3][4][5]. Literature review Human-computer interaction is defined as a technology that realizes the dialogue between human and computer in effective ways and that studies computer, human kinds, and their mutual influence.…”
Section: Introductionmentioning
confidence: 99%
“…Trainers can foster their rhythms through the interaction with the computer. With our approaches, the digitalization and informatization of basic aerobics training and other training levels can be further developed [3][4][5]. …”
mentioning
confidence: 99%